Visi dan Prospek Masa Depan Hubungan Masyarakat (Humas) Dalam Kehidupan Bermasyarakat - Shobri, Jami; Masnawati, Eli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Public relations (PR) has undergone significant transformation along with technological development and social change. This article explores the vision and future prospects of public relations using the library research method. By analyzing various literature sources, this study aims to describe the direction and challenges facing public relations in the digital era. The findings show that PR in the future will be increasingly integrated with digital technology, requiring PR professionals to adapt to changes and develop new skills. The research also provides recommendations for PR practitioners to remain relevant and effective in the face of the changing dynamics of the communications environment.